Molecular Epidemiology of Giardia, Blastocystis and Cryptosporidium among Indigenous Children from the Colombian Amazon Basin - Sánchez, Angie; Munoz, Marina; Gómez, Natalia; Tabares, Juan; Segura, Laura; Salazar, Ángela; Restrepo, Cristian; Ruíz, Miguel; Reyes, Patricia; Qian, Yuchen; Xiao, Lihua; López, Myriam C.; et al. (Frontiers in Microbiology, 2017)
The incidence and prevalence of intestinal parasites in children is most likely due to lack of natural or acquired resistance and differences in behavior and habits closely related to environmental and socioeconomic determinants. The most important protozoa that parasitize humans are Giardia, Entamoeba, Blastocystis and Cryptosporidium. These parasites present wide intraspecific genetic diversity and subsequently classified into assemblages and subtypes. The Amazon basin is the largest in the world and is the fifth freshwater reserve on the planet. Contradictorily, people living in these areas (Indigenous populations) have poor quality of life, which favors the infection of diseases of fecal-oral transmission. The aim of this work was to unravel the molecular epidemiology of Giardia, Blastocystis and Cryptosporidium across four communities (Puerto Nariño, San Juan del Soco, Villa Andrea and Nuevo Paraíso). We obtained 284 fecal samples from children under 15 years old that were analyzed by direct microscopy (261 samples) and Real Time PCR (qPCR) (284 samples). The positive samples for these protozoa were further characterized by several molecular markers to depict assemblages and subtypes. We observed a frequency of Giardia infection by microscopy of 23.7% (62 samples) and by qPCR of 64.8% (184 samples); for Blastocystis by microscopy of 35.2% (92 samples) and by qPCR of 88.7% (252 samples) and for Cryptosporidium only 1.9% (5 samples) were positive by microscopy and qPCR 1.8% (5 samples). Regarding the Giardia assemblages, using the glutamate dehydrogenase (gdh) marker we observed AI, BIII and BIV assemblages and when using triose phosphate isomerase (tpi) we observed assemblages AI, AII, BIII and BIV. In contrast, Blastocystis STs detected were 1, 2, 3, 4 and 6. Lastly, the species C. viatorum, C. hominis (with the subtypes IdA19 and IaA12R8) and C. parvum (with the subtype IIcA5G3c) were identified. We observed a high profile of zoonotic transmission regarding the Giardia assemblages and Blastocystis STs/alleles. Also, we highlight the elevated frequency of infection by these two protozoans suggesting an active transmission in the area. Our findings reinforces the need to deploy better epidemiological surveillance systems for enteric pathogens in the area.